Saweran Tradition in Bogor: A Sociological Analysis of the Dynamics of Social Relationships in Traditional Weddings - Muhamad Rizqi Mustagfiri (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This study aims to analyze the tradition of saweran in marriage with a sociological approach. Saweran, a tradition in Indonesian weddings, is not only a cultural practice, but also reflects the social structure, interactions between individuals, and power dynamics in society. A sociological approach is used to understand how the saweran tradition is reflected in various social aspects, including social structure, social roles, social interaction, power and social control, as well as the potential for conflict and negotiation. This research involved data collection through participatory observation, interviews, and documentation analysis related to the saweran tradition in the context of marriage in Indonesia. The findings of this research are expected to provide deeper insights into the role and function of the saweran tradition in shaping and maintaining the social fabric of society, as well as its implications for broader social dynamics.